Informal payments in public hospitals in Malawi: the case of Kamuzu Central Hospital - Annette Mphande-Namangale; Isabel Kazanga-Chiumia (BMC, 2021)
Abstract Background Informal payments in public health facilities act as a barrier to accessing quality health services, especially for poor people. This research aimed to investigate informal payments for health care services at Kamuzu Central Hospital (KCH), a public referral hospital in Malawi. Results of this study provide evidence on the prevalence and influencing factors of informal payments for health care so that relevant policies and strategies may be developed to address this problem. Methods This study employed a mixed methods research design. The quantitative study had a sample size of 295 patients and guardians. The qualitative study had 7 key informant interviews (with health workers, health managers and policy makers) and 3 focus group discussions (FGDs) with guardians. Each FGD included 10 participants. Thus, in total, the qualitative sample comprised 52 participants. Quantitative data was analyzed using Excel and STATA. Qualitative data was analyzed using a thematic content analysis approach. Results 80% of patients and guardians had knowledge of informal payments. Approximately 47% of respondents admitted making informal payments to access health services, and 87% of informal payments were made at the request of a health worker. Lack of knowledge, fear and desperation among patients and guardians, low salaries of health workers, and lack of effective disciplinary measures, were reported as key factors influencing informal payments. Regression analysis results showed that occupation and gender were the main determinants of informal payments. Conclusions Informal payments exacerbate inequality in access to free public health services. Particularly, poor people have limited access to health services when informal payments are demanded. This practice is unethical and infringes on people's rights to universal access to health care. There is a need to strengthen the public health care system by formulating deliberate policies that will deter informal payments in Malawi.